Low uptake and poor knowledge of preconception sickle cell trait screening among pregnant women in Bushenyi District, southwestern Uganda: Implications for sustainable development goals - Priscilla Peter Dilli; Emmanuel Obeagu; Andrew Tamale; Theophilus Pius; Danladi Makeri (Preventive Medicine Reports)
Objective: This study aimed to assess the level of knowledge and uptake of preconception sickle cell trait (SCT) screening and identify associated factors among pregnant women in Bushenyi District, Southwestern Uganda. Methods: We conducted a cross-sectional study between May 2024 and July 2024 among 177 pregnant women attending antenatal care services at Kampala International University teaching hospital in Bushenyi district southwestern Uganda. Data was collected using structured questionnaires to assess participants' knowledge of SCT and their screening uptake. Descriptive statistics were used to summarize the data, while the chi-square and multivariable logistic regression were used to explore factors statistically associated with screening uptake while eliminating confounders. Results: At least 13 in 20 (57 %, n = 101) pregnant women in Bushenyi district are not knowledgeable about SCT screening, and education level and region of origin stood out as the predictors (OR = 1.77(95 %CI [1.16–2.76], p = 0.008);(OR = 0.48 (95 %CI [0.29–0.81], p = 0.006). Regarding the uptake of SCTS, only 2.8 % (n = 5) of pregnant women have ever been screened, and their region of origin was the single predictor of SCTS uptake (OR = 0.121; [95 %CI: 0.023–0.636], p = 0.013). Conclusion: Awareness and uptake of preconception SCT screening among pregnant women in Bushenyi District are poor. This study calls for the integration of health education and genetic counseling into antenatal care services, contributing to realizing Sustainable Development Goal 3.2, which seeks to end preventable deaths of newborns and children under 5 years of age by the year 2030.